Considering inter-receiver pseudorange biases for BDS-2 precise orbit determination. (June 2021) - Li, Ran; Li, Zishen; Wang, Ningbo; Tang, Chengpan; Ma, Hongyang; Zhang, Yang; Wang, Zhiyu; Wu, Jiatong
Highlights: The inter-receiver pseudorange bias would cause along-track deviations in GEO satellite orbit determination. POD accuracy improvement of BDS-2 satellites. Inter-receiver bias correction in pseudorange observations. Abstract: The inter-receiver pseudorange biases exist between receivers equipping with different front-end designs and correlator types. It is distinguishable from differential code biases and would affect Global Navigation Satellite System (GNSS) estimations if it is not taken into account in data processing. In this contribution, the effects of inter-receiver pseudorange biases on the regional BeiDou navigation satellite system (BDS-2) satellite precise orbit determination (POD) will be investigated. For validation purposes, 35 globally distributed Multi-GNSS Experiment ground stations for which the receivers are from three manufacturers were used to determine the precise orbits of BDS-2 satellites from day of year 154 to 163, 2017. The accuracy of orbit overlap and satellite laser ranging (SLR) residual validation comparisons show that by implementing inter-receiver pseudorange bias corrections, the POD accuracies of the BDS-2 satellites can be effectively improved. The root mean square errors of 24-h precise orbit determination overlap corresponding to the radial, cross-track, and along-track components are improved by 1.4%, 2.7%, and 12.7%, respectively, after correcting the inter-receiver pseudorange biases. The standard deviations of the SLR residuals of satellite C01, C13, and C11 are reduced from 30.7, 7.1, and 3.5 cm to 30.2, 6.8, and 2.9 cm, respectively. The results also showed that inter-receiver pseudorange biases will cause an along-track bias in Geostationary Earth Orbit (GEO) satellite orbit determination. The performances of GEO POD in along-track component can be improved by considering the inter-receiver pseudorange biases.